Conidiobolomycosis in Ovine in Southeast Bahia - Brazil - Silva, Gisele Dias; Filho, Fernando Alzamora; Ribeiro, Thiago Santos; Santos, Emilly Oliveira; Andrioli, João Luciano; Silva, Fabiana Lessa (Acta Scientiae Veterinariae, 2021)
Background: Conidiobolomycosis is a highly lethal, granulomatous disease that primarily affects the respiratory system of sheep. The etiological agents are fungi of the genus Conidiobolus, including Conidiobolus coronatus, C. incongruus, and C. lamprageus. In Northeast Brazil, this disease is particularly important considering the significant impact sheep and goats have on the regional economy. The present report describes the occurrence of conidiobolomycosis in two sheep from the same property in the Itabuna-BA region that were referred to the Veterinary Hospital of the State University of Santa Cruz, Bahia, Brazil. Case: The primary complaint in both animals was bilateral bloody nasal discharge over a period of approximately 15 days and frequent coughing. On physical examination, the animals exhibited “goosebumps” and opaque hair, with a body score of 1 (scale, 1-5), mild dehydration (7%), apathy, frequent cough with putrid odor, bilateral serosanguinolent nasal discharge, craniofacial asymmetry, expiratory dyspnea, enlargement of the retropharyngeal lymph nodes, audible pulmonary rales, and pain on percussion of the pulmonary field. A therapeutic support protocol was established to stabilize the animals until the results of complete blood count, radiography, and microbiological evaluation of nasal content were available. Definitive diagnosis of disease was made by direct positive mycological examination, that revealed the presence of wide rarely septate hyphae, and isolation and cultivation of the fungus Conidiobolus sp., with microculture on slides and staining with lactophenol blue cotton. Due to disease diagnosis and the severity of injuries observed, the prognoses of both animals were considered to be unfavorable and led to euthanasia and necropsy. At necropsy, the most relevant findings were granulomatous rhinitis with ascending inflammatory processes to the meninges and adjacent structures, in addition to cranioventral areas of pulmonary consolidation with drainage of purulent exudate at the cut surface, suggestive of bronchopneumonia. Histopathology revealed intense pyogranulomatous inflammation associated with the presence of hyphae in negative images within the cytoplasm of multinucleated giant cells in the nasal cavity, lungs, meninges, and brain. Discussion: The association of necropsy findings, histopathological changes, and microbiological isolation of the fungus facilitated understanding of the changes observed in the respiratory system and other organs, and enabled correlation between the recorded lesions and clinical manifestations exhibited by the animals. Based on the lesions observed clinically and at necropsy, both cases were diagnosed with rhinopharyngeal conidiobolomycosis. The histopathological and macroscopic changes observed were similar to what are often described in severe cases of the disease. Considering the severity of the disease and its high lethality in these animals, conidiobolomycosis can lead to significant damage of the production chain; this was observed in the present property, where three animals in a herd of 20 died with signs of the disease, highlighting the importance of the disease, particularly in the Northeast region, where the largest flocks of sheep are found in Brazil. The implementation of prophylactic measures is particularly important considering the unfavorable prognosis and the absence of effective treatments.